Retracted: Evaluation of the predictive performance of the principal component two‐parameter estimator. (7th June 2018) - Li, Rong; Li, Fei; Huang, Jiewu
Abstract: Retraction: Li R, Li F, Huang J. Evaluation of the predictive performance of the principal component two‐parameter estimator. Concurrency Computat Pract Exper . 2019;31:e4710.https://doi.org/10.1002/cpe.4710 The above article, published online on 7th June 2018 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor, Professor Geoffrey Fox, and John Wiley and Sons Ltd. The retraction has been agreed due to inaccuracies in the formula derivation resulting in foundational errors throughout the article that are beyond the scope of an erratum.